Candida krusei isolated from fruit juices ultrafiltration membranes promotes colonization of Escherichia coli O157:H7 and Salmonella enterica on stainless steel surfaces - Tarifa, Maria Clara (2017)
To clarify the interactions between a common food spoilage yeast and two pathogenic bacteria involved in outbreaks associated with fruit juices, the present paper studies the effect of the interplay of Candida krusei, collected from UF membranes, with Escherichia coli O157:H7 and Salmonella enterica in the overall process of adhesion and colonization of abiotic surfaces. Two different cases were tested: a) co-adhesion by pathogenic bacteria and yeasts, and b) incorporation of bacteria to pre-adhered C. krusei cells. Cultures were made on stainless steel at 25°C using apple juice as culture medium. After 24 h of co-adhesion with C. krusei, both E. coli O157:H7 and S. enterica increased their counts 1.05 and 1.11 log CFU cm2, respectively. Similar increases were obtained when incorporating bacteria to pre-adhered cells of Candida. Nevertheless C. krusei counts decreased in both experimental conditions, in a) 0.40 log CFU cm2 and 0.55 log CFU cm2 when exposed to E. coli O157:H7 and S. enterica and in b) 0.18 and 0.68 log CFU cm2, respectively. This suggests that C. krusei, E. coli O157:H7, and S. enterica have a complex relationship involving physical and chemical interactions on food contact surfaces. This study supports the possibility that pathogen interactions with members of spoilage microbiota, such as C. krusei, might play an important role for the survival and dissemination of E. coli O157:H7 and Salmonella enterica in food-processing environments. Based on the data obtained from the present study, much more attention should be given to prevent the contamination of these pathogens in acidic drinks.